Perbedaan Berpikir Kritis Antara Siswa Yang Diajar Dengan Menggunakan Bahan Ajar LKS Berbasis Model Berpikir Induktif dan Model Induktif Kata Bergambar Pada Mata Pelajaran IPA Kelas IV SDM di Kota Bengkulu - Sukarno Sukarno; Salamah Salamah (Manhaj: Jurnal Penelitian dan Pengabdian Masyarakat, 2019)
This study aims to determine differences in students' critical thinking by using science-based LKS teaching materials based on inductive thinking models with Inductive Word Pictorial models in class IV SDM II of Bengkulu City, critical thinking differences from groups of students with high initial ability using teaching materials based on science-based LKS inductive thinking with the pictorial word Inductive model in class IV SDM II Bengkulu City, the difference in critical thinking from the group of students with low initial ability by using science teaching material based on inductive thinking models with the Inductive Word Pictorial model in class IV SDM II Bengkulu City, the interaction between learning model and the initial ability to think critically in class IV SDM II Bengkulu City. This study uses a quantitative approach to the type of quasi-experimental research. The subjects of this study were HR II students, totaling 40 students. Data collection was performed using essay tests. The results showed 1) Overall there were differences in students' critical thinking between those taught by using teaching materials for science subjects based on the learning model of inductive thinking and based on the pictorial model of pictorial words. . 2) there is a difference in the critical thinking of students with high initial ability between those taught by using teaching materials for science subjects based on inductive thinking learning models and based on the pictorial model of pictorial words. 3) there is no difference in the critical thinking of students with low initial ability between those taught by using teaching materials based on natural science learning models based on inductive thinking models and based on the pictorial model of pictorial words. students in science subjects at SD Muhammadiyah II Bengkulu city.